2019
DOI: 10.1002/ijop.12636
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of individual, community and national resiliencies of Israeli Jews and Arabs

Abstract: The contribution of individual characteristics to predicting individual, community and national resilience of Israeli Jews and Arabs was investigated. Psychological resilience refers to people's assessment of their ability to withstand negative psychological consequences of major afflictions, and to keep functioning despite these adversities. The following hypotheses were examined: 1. The Jewish sample would score higher than the Arab sample on indices of individual, community and national resilience. 2. Men o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…To better understand the trends of the population’s resilience, distress, and subjective well-being over time, the current two repeated measurements were compared with previous research results, which were based on a representative sample of the Israeli population. These findings show the resilience and distress levels of the Israeli population as found in 2018, during a relatively quiet period in terms of security risks, thus representing a baseline measurement [ 24 ].…”
Section: Methodsmentioning
confidence: 91%
“…To better understand the trends of the population’s resilience, distress, and subjective well-being over time, the current two repeated measurements were compared with previous research results, which were based on a representative sample of the Israeli population. These findings show the resilience and distress levels of the Israeli population as found in 2018, during a relatively quiet period in terms of security risks, thus representing a baseline measurement [ 24 ].…”
Section: Methodsmentioning
confidence: 91%
“…NR refers to the ability of a nation to deal with its crises while keeping its social fabric intact (Canetti, Waismel-Manor, Cohen, & Rapaport, 2014), and is comprised of the four major components of patriotism, optimism, social integration, and trust in political and public institutions (Ben-Dor, Pedahzur, Canetti-Nisim, & Zaidise, 2002). Israel has been a pioneering context in NR research and findings point to these components as leverage to Israel's ability to cope with half a decade of Israel-Palestinian conflict (Elran, 2006;Gal, 2014) Cross-national studies on NR began quite recently (Kimhi et al, 2018) and findings concur that the concept of NR is an important factor for nations that are dealing with adversities (Marciano, Kimhi, & Eshel, 2019).…”
Section: National Resiliencementioning
confidence: 99%
“…Previous studies have found that the demographic characteristics of age, gender, and family income have predicted stress and resilience, primarily in the context of security threats ( Eshel & Kimhi, 2016 ; Marciano, Eshel, & Kimhi, 2019 ). Another study has reported a significant association between the size of the community and community resilience ( Kimhi, Goroshit, & Eshel, 2013 ).…”
Section: Introductionmentioning
confidence: 99%